Building workforce capacity for effective use of health information systems: Evaluation of a blended eLearning course in Namibia and Tanzania. (November 2019) - Rudd, Kristina E.; Puttkammer, Nancy; Antilla, Jennifer; Richards, Janise; Heffron, Matthew; Tolentino, Herman; Jacobs, Daniel J.; KatjiuanJo, Puumue; Prybylski, Dimitri; Shepard, Mark; Kumalija, John Claud; Katuma, Happiness Lazaro; et al.
Abstract: Background: Electronic health information systems (HIS) are critical components of national health systems, and have been identified as a key element in the development and strengthening of health systems globally. Novel approaches are needed to effectively and efficiently train health care workers on the use of HIS. One such approach is the use of digital eLearning programs, either alone or blended with face-to-face learning activities. Methods: We developed a novel blended eLearning course based on an in-person HIS training package previously developed by the United States Centers for Disease Control and Prevention. We then conducted a pilot implementation of the eLearning course in Namibia and Tanzania. Results: The blended eLearning pilot program enrolled 131 people, 72 (55%) from Namibia and 59 (45%) from Tanzania. The majority of enrollees were female ( n = 88, 67%) and were nurses ( n = 66, 50%). Of the 131 people who participated in the in-person orientation, 95 (73%) completed some or all of the eLearning modules. Across all three modules, the mean score on the post-test was significantly greater than on the pre-test (p < 0.001). When comparing results from previous in-person workshops and the blended eLearning course, we found that participants experienced strong learning gains in both, although learning gains were somewhat greater in the in-person course. Blended eLearning course participants reported good to very good satisfaction with the overall content of the course and with the eLearning modules (3.5 and 3.6 out of 5-point Likert scale). We estimate that the total cost per participant is 2.2–3.4 times greater for the in-person course (estimated cost USD 980) than for the blended eLearning course (estimated cost USD 287-437). Conclusion: A blended eLearning course is an effective method with which to train healthcare workers in the basic features of HIS, and the cost is up to 3.4 times less expensive than for an in-person course with similar content.